Islamic Digital Literacy and Character Formation in the Cyber Era: Integrating the Concepts of Adab, Akhlaq, and Social Media Ethics into a Digital-Based Islamic Education Curriculum - Mukhlis Mukhlis; Ani Cahyadi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze and formulate an integrative model of Islamic digital literacy in shaping students’ character through a digital-based Islamic Religious Education (PAI) curriculum. The primary focus of this research is to integrate the concepts of adab (proper conduct), akhlak (moral character), and social media ethics as normative and operational foundations in responding to the challenges of the cyber era, including misinformation, hate speech, ideological polarization, and digital radicalism. The study also seeks to identify the interconnection between Islamic value concepts, digital risks, ethical strategies, and the formulation of an applicable curriculum across educational levels, this research employs a library research method with a qualitative-descriptive and analytical approach. Data sources were derived from classical and contemporary literature on Islamic education, digital literacy theory, character education, religious moderation, as well as national and international educational policy documents, including the digital literacy framework developed by UNESCO. The data were analyzed through stages of identification, thematic classification, conceptual comparison, and integrative synthesis to construct a systematic theoretical framework. The validity of the study was ensured through source triangulation and consistency in normative and pedagogical argumentation, the findings indicate that Islamic digital literacy has a conceptual structure consisting of three main foundations: adab as normative awareness, akhlak as internalized character formation, and social media ethics as practical application within digital spaces. These elements can be integrated into the PAI curriculum through project-based learning focused on information verification (tabayyun), simulations of ethical digital discussions, critical analysis of online narratives, and education on digital security and responsibility. This model emphasizes that a digital-based PAI curriculum functions not merely as a means of transferring religious knowledge, but also as an instrument for character formation that is adaptive to technological developments.